Karakteristik Minyak Sereh Wangi dengan Umur Panen Daun dan Lama Destilasi - Karneta, Railia; Wahyuni, Reshi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Karneta R, Reshi W. 2020. Characteristics of sereh wangi oil with leaf harvest age and long distillation. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang Â 20 Oktober 2020. pp. xxx.Â Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Fragrant lemongrass (Cymbopogon nardus L.Rendle) is a grass plant, originally potential to prevent soil erosion and rehabilitating critical lands, it turns out that this plant contains essential oils from the leaves and stems which is very potential to be used by the pharmaceutical and cosmetic industries. This study aims to determine the effect of harvesting time and time of distillation process on the characteristics of citronella oil produced. This study used a randomized block design arranged in a factorial which consists of two factors, namely the age of harvest of fragrant lemongrass leaves (4 and 6 months) and distillation time (3,4,5,6 hours), with 8 treatment combinations, and three replications. Implementation of research on CV Alam Palindra Agro, komplek kavling Palindra Green City Indralaya Ogan Ilir. The results of the study are harvest age of 4 months of fragrant lemongrass leaves gives the best results against yield, geraniol, citronellal, specific gravity and refractive index. The distillation time was treated for 5 hours gives the best results against yield, geraniol, citronellal, specific gravity and refractive index. The interaction between harvesting age of 4 months of citronella leaves and 5 hours of distillation time give the best influence on yield, geraniol, citronellal, and specific gravity but the best refractive index at 6 months of harvest. The conclusion is harvest age 4 months and distillation 5 hours provide the best yieldand quality of lemongrass oil.